Pemberdayaan Desa Wisata Geosite Pelangas, Bangka Barat berdasarkan Teori Analisis TALC (Tourism Area Life Cycle) - Lestari, Zakia Ayu; Prima, Anugrah; Saputri, Irghea; Lagalo, Anggraeni M.S (Tulisan Ilmiah Pariwisata (TULIP), 2023)
Research on the development conditions of the Pegawi tourism Village base on the TALC (Tourism Area Life Cycle) analysis theory is descriptive qualitative study. The research location was determined purposively in Pelangas village, with the consideration that the Pelangas village was the winner number 3 of competition tourism village Bangka Belitung Island. The purpose of this study was the investigage the process of empowering Pegawi tourism village and indetify the development based on theory TALC. The results showed that process of empowering Pelangas Hilss went through 3 stages, namely the stage of awerness, breathing and power. These thre stage were passed with the resuly that most of the people of Pelangas Village join Pokdarwis and negative behaviour began to wear off. Keywords: Tourism Village.Community Empowerment, TALC